Does lock-down of Wuhan effectively restrict early geographic spread of novel coronavirus epidemic during chunyun in China? A spatial model study - Yi Hu; Lingcai Kong; Tong Yao; Xinda Chen; Wei Du (BMC, 2021)
Abstract Background Prior to Wuhan lock-down in 2020, chunyun, the largest population mobility on this planet, had begun. We quantified impact of Wuhan lock-down on COVID-19 spread during chunyun across the nation. Methods During the period of January 1 to February 9, 2020, a total of 40,278 confirmed COVID-19 cases from 319 municipalities in mainland China were considered in this study. The cross-coupled meta-population methods were employed using between-city Baidu migration index. We modelled four scenarios of geographic spread of COVID-19 including the presence of both chunyun and lock-down (baseline); lock-down without chunyun (scenario 1); chunyun without lock-down (scenario 2); and the absence of both chunyun and lock-down (scenario 3). Results Compared with the baseline, scenario 1 resulted in 3.84% less cases by February 9 while scenario 2 and 3 resulted in 20.22 and 32.46% more cases by February 9. The geographic distribution of cases revealed that chunyun facilitated the COVID-19 spread in the majority but not all cities, and the effectiveness of Wuhan lock-down was offset by chunyun. Impacts of Wuhan lock-down during chunyun on the COVID-19 spread demonstrated heterogenetic geographic patterns. Conclusion Our results strongly supported the travel restriction as one of the effective responses and highlighted the importance of developing area-specific rather than universal countermeasures.